Some remarks on the crafts of the Ustrushana peoples - Mominova Gulchekhra Ismailovna; Tugalov Bakhodir Bobur oglu (Genius Journals, 2022)
There is information about the study of applied arts and crafts of the peoples of the Ustrushanas region according to written sources and archaeological data.
Keywords: Pottery; tools; handicraft; Pardakultepa